Palm Phytoliths of Mid-Elevation Andean Forests - Huisman, Seringe N.; Raczka, M. F.; McMichael, Crystal N. H. (Frontiers in Ecology and Evolution, 2018)
Palms are one of the most common tropical plant groups. They are widespread across lowland tropical forests, but many found in higher altitudes have more constrained environmental ranges. The limited range of these species makes them particularly useful in paleoecological and paleoclimate reconstructions. Palms produce phytoliths, or silica structures, which are found in their vegetative parts (e.g. wood, leaves, etc). Recent research has shown that several palms in the lowland tropical forests produce phytoliths that are diagnostic to the sub-family or genus-level. Here we characterize Andean palm phytoliths, and determine whether many of these species can also be identified by their silica structures. All of our sampled Andean palm species produced phytoliths, and we were able to characterize several previously unclassified morphotypes. Some species contained unique phytoliths that did not occur in other species, particularly Ceroxylon alpinium, which is indicative of specific climatic conditions. The differences in the morphologies of the Andean species indicate that palm phytolith analysis is particularly useful in paleoecological reconstructions. Future phytolith analyses will allow researchers to track how these palm species with limited environmental ranges have migrated up and down the Andean slopes as a result of past climatic change. The phytolith analyses can track local-scale vegetation dynamics, whereas pollen, which is commonly used in paleoecological reconstructions, reflects regional-scale vegetation change.